'Selling the creative city': Wellington tourism film in the neoliberal era. Issue 2 (2nd September 2019) - Bonelli, Diego; Jutel, Thierry; Leotta, Alfio
ABSTRACT: Since the beginning of the Twentieth Century tourism films have constituted a significant part of New Zealand film production. In fact, films made and/or used for tourism promotion have been released for domestic and overseas circulation by both government-led and private film production companies. Over the last 10 years the institutions in charge of Wellington tourism marketing have been increasingly relying on social media platforms such as Youtube and Facebook to globally circulate images of New Zealand's capital city. Indeed, since 2007, 20 tourism marketing campaigns conceived for social media circulation featured in WellingtonNZ Youtube channel. This article will focus on three of these campaigns: the Vampire's Guide to Vellington (2014); the It's Never Just a Weekend When It's in Wellington series (2014) and the LookSee series (2017). Through the analysis of these case studies, this article argues that contemporary Wellington tourism film production is a complex and multilayered process characterised by the cross-collaboration between local political stakeholders, local creatives and local businesses. Moreover, it highlights how the representation of Wellington as a cinematic and creative city, home of a globalised creative class has been informed by the neoliberal paradigm and by the persistence of a deeply-rooted settler gaze.